A new species of allophryne (anura: allophrynidae) from the atlantic rain forest biome of eastern Brazil - Caramaschi, Ulisses; Orrico, Victor G. D. [UNESP]; Faivovich, Julian; Dias, Iuri Ribeiro; Sole, Mirco (Herpetologists League, 2013)
A new species of the genus Allophryne is described and, in contrast to its congeners that occur in the Amazon Basin, is based on specimens obtained in Urucuca, State of Bahia, in the Atlantic Rain Forest of eastern Brazil. Allophryne relicta sp. nov. is characterized by a medium body size for the genus (snout-vent length range 19.9-21.9 mm in males); large head (head width about 35% of SVL); large, red-orange eyes, with a large black transversal stripe on iris; dorsum covered by few tubercles and many scattered black dots; dorsolateral surfaces cream with dark brown, elongate, anastomosed spots, and venter clear gray with scattered small white tubercles; presence of a line of tubercles on the ventrolateral surface of forearm; advertisement call formed by a multi-pulsed note of 0.509 +/- 0.029 s in duration and emitted at intervals of 1.287 +/- 0.500 s, with notes composed of 28.58 +/- 1.84 pulses at a dominant frequency of 3828 +/- 82.28 Hz; call-note emission rate of 34.46 notes/min and pulse emission rate of 56.13 +/- 1.25 s. The molecular phylogeny supports the placement of A. relicta sp. nov. as sister taxon of a clade formed by A. resplendens + A. ruthveni.
Keywords: Allophryne relicta sp nov.; Amphibia; Taxonomy